Assessment of Pre And Post Procedural Quality of Life In Successful Percutaneous Transvenous Mitral Commissurotomy Patient - Mukarram, Shahid; Shabbir, Muhammad; Mushtaq, Huma; Ahmad, Hira; Ahmad, Ayaz; Atta ul Haq, Ahmed; Essa, Muhammad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the effect of successful Percutaneous Transvenous Mitral Commissurotomy (PTMC) on clinical status and Quality of Life (QOL) in patients with severe rheumatic mitral stenosis applying the WHOQOL-BREF questionnaire. Study Design: Analytical cross-sectional research. Place and Duration of Study: Cardiology Department, Armed Forces Institute of Cardiology/National Institute of Heart Diseases (AFIC/NIHD), Rawalpindi, Oct-Dec 2025 Methodology: Thirty-five patients aged 15–65 years with symptomatic severe rheumatic mitral stenosis undergoing successful PTMC were enrolled using non-probability consecutive sampling. Patients with left atrial thrombus, Wilkins score >8, moderate–severe MR, significant AVD, or unsuccessful PTMC were excluded. The quality of life was checked one day before and again one month after PTMC using WHOQOL-BREF. The patient’s clinical status was evaluated by the NYHA classification; p-value below 0.05 was considered significant. Results: A total of 35 patients were included in the study. In patients under 40 years, the WHOQOL-BREF scores were 25.71 ± 1.93 for the physical domain, 22.0 (20.0–23.0) for the psychological domain, 12.0 (11.0–13.0) for the social domain, and 29.0 (28.0–35.0) for the environmental domain, with a total score of 88.0 (82.0–97.0). Quality of life improved significantly in all domains (p < 0.001), with total scores increased from 52.0 (48.0–57.0) to 86.0 (81.0–95.0) after the procedure Conclusion: PTMC is a reliable and effective treatment option for patients with severe rheumatic mitral stenosis. The study shows that PTMC leads to clear improvement in mitral valve performance, functional capacity, and patients’ perceived quality of life.